2013
DOI: 10.1093/humupd/dmt038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined oral contraception on testosterone levels in healthy women: a systematic review and meta-analysis

Abstract: BACKGROUNDCombined oral contraceptives (COCs) reduce levels of androgen, especially testosterone (T), by inhibiting ovarian and adrenal androgen synthesis and by increasing levels of sex hormone-binding globulin (SHBG). Although this suppressive effect has been investigated by numerous studies over many years, to our knowledge no systematic review concerning this issue had been performed. This systematic review and meta-analysis was performed to evaluate the effect of COCs on concentrations of total T, free T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(183 citation statements)
references
References 111 publications
(270 reference statements)
14
151
2
6
Order By: Relevance
“…By contrast with this prediction, we observed only an effect of testosterone in the current study, suggesting that our results are not simply due to the effects of experiencing intrasexual competition on hormone levels. Our proposal that our results are more likely to reflect the effects of testosterone on intrasexual competitiveness (rather than vice versa) is also supported by Cobey et al's (2013) results indicating that partnered women's intrasexual competitiveness decreased once they started using hormonal contraceptives, which would lower their testosterone levels (Zimmerman et al, 2014). It is also consistent with research reporting that exogenous testosterone increases intrasexual competitiveness in female birds and rats (e.g., Albert et al, 1990;Zysling et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By contrast with this prediction, we observed only an effect of testosterone in the current study, suggesting that our results are not simply due to the effects of experiencing intrasexual competition on hormone levels. Our proposal that our results are more likely to reflect the effects of testosterone on intrasexual competitiveness (rather than vice versa) is also supported by Cobey et al's (2013) results indicating that partnered women's intrasexual competitiveness decreased once they started using hormonal contraceptives, which would lower their testosterone levels (Zimmerman et al, 2014). It is also consistent with research reporting that exogenous testosterone increases intrasexual competitiveness in female birds and rats (e.g., Albert et al, 1990;Zysling et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, intrasexual competitiveness did not differ between these late-follicular or mid-luteal phases. Since hormonal contraceptive use lowers testosterone levels in women (Zimmerman et al, 2014) and evidence that testosterone levels change between the late-follicular and mid-luteal phases is mixed (Dabbs, 1990;Dabbs & de La Rue, 1991; see also Caruso et al, 2014), Cobey et al (2013) speculated that the observed changes in women's intrasexual competitiveness may be a consequence of changes in their testosterone levels. Indeed, this explanation would be consistent with findings showing that women's testosterone levels increased after they imagined their partner flirting with an attractive woman (Ritchie & van Anders, 2014) or were exposed to olfactory cues associated with ovulation in other women (Maner & McNulty, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that OC use reduced free testosterone by 61% compared to non-users 44 , possibly due to an increase in sex hormone binding globulin concentration, which binds to testosterone rendering it inactive. OC use increases GH concentrations [45][46] with second (30 µg EE and 0.125 mg Levonorgestrel) and fourth generation (30 µg EE and 2 mg Dienogest) OCs reducing concentrations of IGF-1, but not a ecting IGF binding protein-1 concentrations 45 .…”
Section: Is There a Relationship Between Hormonal Contraceptives And mentioning
confidence: 99%
“…In addition, we have shown earlier that a dose of 50 mg DHEA could normalize free T levels in combination with a COC containing the progestin levonorgestrel (LNG) [53]. COCs containing LNG hardly increase SHBG [19] and therefore, the clinical effect of androgen restoration in users of an EE/LNG COC by adding 50 mg DHEA may be more pronounced. For those COCs that increase SHBG, a higher dose of DHEA may be required to normalize free T and demonstrate clinical effects.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…COCs are known to reduce androgen levels, especially T [19,20], although no consistent effect on mood and sexual function has been observed [3,[21][22][23][24][25][26]. However, reduced androgen levels may be an important factor contributing to COC-associated sexual dysfunction and mood complaints [27,28].…”
Section: Introductionmentioning
confidence: 99%